Vegetation and microbial determinants of soil carbon isotopic composition - Nel, Jacques A (Department of Biological Sciences, 2018)
Typically, soil δ¹³C and δ¹⁵N values tend to increase with depth across a wide range of ecosystems. Changes in δ¹³C with depth have been attributed to vegetation changes (i.e. C₃/C₄ shifts), but the similarity in δ¹³C and δ¹⁵N profiles suggest that microbial decomposition may play an important role. The determinants of soil δ¹³C and δ¹⁵N, however, are complex and microbial decomposition and vegetation shifts are not the only mechanisms that drive the fractionation of the isotopes with depth. We explored the utility of using δ¹³C as a proxy for vegetation change by considering alternative mechanisms for the changes in soil δ¹³C with depth. These alternate mechanisms may weaken the interpretation of soil δ¹³C as an indicator of vegetation change if the measured δ¹³C changes are small. We hypothesized that: (1) if soil-related processes such as mineralization and dark CO₂-fixation by microbes and roots contribute significantly to the δ¹³C signature of bulk soil at depth, one cannot simply determine whether the δ¹³C value of the soil at depth is indicative of a past vegetation assemblies (i.e. C₃/C₄ transitions); (2) changes in soil δ¹³C and δ¹⁵N values are linked through common microbially mediated decomposition-related processes; (3) anaplerotic CO₂ fixation by microbes and roots may contribute significantly to soil δ¹³C values, while N₂-fixation may contribute to soil δ¹⁵N values with depth. Microbial processing of SOM during decomposition leads to ¹³C-enrichement of SOM with depth and has been modelled using a Rayleigh distillation process. Anaplerotic fixation of soil CO₂ is, however, known to occur in microbes and roots and we suggest that this has a role in determining soil SOM δ¹³C values through cumulative incorporation of bulk atmosphere CO₂ into SOM. These processes vary greatly between soils and environments. The correspondence between soil δ¹³C and δ¹⁵N was assessed by compiling data from soil depth profiles from widely distributed sites and conducting an analysis of global δ¹³C and δ¹⁵N variations in surface soils in order to determine relationships between soil isotopes and with climate and soil properties. Strong positive correlations between δ¹³C and δ¹⁵N values through soil profiles were found at a number of sites and were found to be independent of vegetation type. Globally, soil δ¹³C and δ¹⁵N values were also found to be significantly positively correlated across a wide range of climates and biomes. The global correspondences between δ¹³C and δ¹⁵N values may suggest a mechanistic link between δ¹³C and δ¹⁵N through the process of SOM decomposition and microbial processing. Anaplerotic CO₂ fixation by soil microbes and roots was assessed using soils from 10 sites across South Africa differing in soil properties and incubated in the dark for 3 d under continuous exposure to ¹³CO₂- and ¹⁵N₂-enriched atmospheres with varying soil moisture (10, 50 and 100% of field capacity) and temperature (4, 25, 40°C). There was no evidence of significant N₂ fixation in any treatment. Significant soil anaplerotic CO₂ fixation, however, occurred in all soils. Highest rates of anaplerotic CO₂ fixation occurred in soils at 50% field capacity and 25°C, suggesting a link with microbial biotic activity. Soils with low C and N concentrations and low C:N ratios exhibited the highest rates of CO₂ fixation in soils, indicating a link between anaplerotic CO₂ fixation rates and soil nutrient status. The higher rates of CO₂ fixation in soils with low nutrients may indicate that soil microbes rely increasingly on anaplerotic fixation as SOM-N declines, forcing greater reliance on de novo amino acid synthesis, and thus anaplerotic CO₂ fixation. The ubiquitous occurrence of anaplerotic ¹³CO₂ fixation in these soils indicates that anaplerotic fixation is likely important in contributing to determining soil δ¹³C values. Diffusion of low δ¹³C bulk atmospheric CO₂ (ca. -10‰) into the soil atmosphere (<< -10‰) will drive soil CO₂ δ¹³C towards ca. -10‰, and constant anaplerotic CO₂ fixation will result in SOM δ¹³C also tending towards 10‰ in more highly processed SOM deeper in the soil. The consequences of decomposition and the linked anaplerotic activity for soil δ¹³C values may be erroneously interpreted as evidence for C₄ vegetation being invaded by C₃ vegetation, potentially leading to incorrect conservation decisions. We argue that δ¹³C should only be used as a proxy for vegetation change where decomposition rates and anaplerotic CO₂ fixation are low and/or their effect on soil δ¹³C values can be accounted for.